Translational bioethics as a two-way street. Developing clinical ethics support instruments with and for healthcare practitioners - Metselaar, Suzanne (Bioethics, 2024)
This article discusses an approach to translational bioethics (TB) that is concerned with the adaptation—or ‘translation’—of concepts, theories and methods from bioethics to practical contexts, in order to support ‘non-bioethicists’, such as researchers and healthcare practitioners, in dealing with their ethical issues themselves. Specifically, it goes into the participatory development of clinical ethics support (CES) instruments that respond to the needs and wishes of healthcare practitioners and that are tailored to the specific care contexts in which they are to be used. The theoretical underpinnings of this participatory approach to TB are found in hermeneutic ethics and pragmatism. As an example, the development of CURA, a low-threshold CES instrument for healthcare professionals in palliative care, is discussed. From this example, it becomes clear that TB is a two-way street. Practice may be improved by means of CES that is effectively tailored to specific end users and care contexts. The other way around, ethical theory may be enriched by means of the insights gained from engaging with practice in developing CES in a process of co-creation. TB is also a two-way street in the sense that it requires collaboration and commitment of both bioethicists and practitioners, who engage in a process of mutual learning. However, substantial challenges remain. For instance, is there a limit to the extent to which a method of moral reasoning can be adapted in order to meet the constraints of a given healthcare setting? Who is to decide, the bioethicist or the practitioners?